Perioperative Challenges in Repeat Bladder Exstrophy Repair - Case Report - Etta, Otu Enenyi (Open Access Maced J Med Sci, 2015)
Bladder exstrophy is a rare congenital malformation. It presents as leakage of urine in the anterior abdominal wall following defects in midline anterior abdominal wall skin and bladder. We report the use of combined general anaesthesia and caudal epidural analgesia in a 4yr old boy for repeat bladder exstrophy repair. Problems of prolonged surgery and the challenges of pain and sedation management in the post operative period are discussed.